Reliability and reserve in competitive electricity market scheduling. - Flynn, M. (IEEE Transactions on power systems)
Power systems are typically scheduled at least cost subject to operational and security constraints. Generally, no account is taken of generator reliability when scheduling units. Also, the security criteria, which include reserve, are usually deterministic in nature. This paper proposes a method to consider generator reliability explicitly in the scheduling problem. A competitive structure is proposed which includes a market for reserve. This is formulated as an augmented Lagrangian dual function and is solved using a new recurrent neural network. The price for reserve is used, along with the unit reliability, to find a balance between the cost of reserve and the risk of not providing it